The effects of sodium bicarbonate (NaHCO3) ingestion on high intensity cycling capacity - Higgins, M. F.; James, R. S.; Price, M. J. (Journal of Sports Sciences, 2013)
Ten healthy, non-cycling trained males (age: 21.2 ± 2.2 years, body mass: 75.9 ± 13.4 kg, height: 178 ± 6 cm, VO2PEAK: 46 ± 10 ml · kg·min) performed a graded incremental exercise test, two familiarisation trials and six experimental trials. Experimental trials consisted of cycling to volitional exhaustion at 100%, 110% and 120% WPEAK, 60 min after ingesting either 0.3 g·kg body mass sodium bicarbonate (NaHCO3) or 0.1 g/kg body mass sodium chloride (placebo). NaHCO3 ingestion increased cycling capacity by 17% at 100% WPEAK (327 vs. 383 s; P = 0.02) although not at 110% WPEAK (249 vs. 254 s; P = 0.66) or 120% WPEAK (170 vs. 175 s; P = 0.60; placebo and NaHCO3 respectively). Heart rate (P = 0.02), blood lactate (P = 0.001), pH (P < 0.001), [HCO3 -], (P < 0.001), and base excess (P < 0.001) were greater in all NaHCO3 trials. NaHCO3 attenuated localised ratings of perceived exertion (RPEL) to a greater extent than placebo only at 100% WPEAK (P < 0.02). Ratings of abdominal discomfort and gut fullness were mild but higher for NaHCO3. NaHCO3 ingestion significantly improves continuous constant load cycling at 100% WPEAK due to, in part, attenuation of RPEL.